Analysis of the QS. Ar-Rum Verse 41 on the Tsunami Disaster Issue for UNP Students - Ajat Hidayat; Ahmad Aziz; Pela Safni; Erman; Radhiatul Hasnah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Padang State University is located in the earthquake and tsunami danger zone. On the other hand, the attitude and curiosity of Padang State University students regarding disaster mitigation are still lacking. Apart from that, the level of implementation of knowledge about disaster mitigation by the government and related agencies is also lacking. This research aims to describe the attitudes of Padang State University students towards mitigating the earthquake and tsunami disaster in the city of Padang. This research is quantitative descriptive research which is used to study an event or phenomenon as it is. The type of data in this research is primary data obtained directly from the research object by submitting a questionnaire to students and secondary data from various books and articles related to the research. The data collection techniques used in this research are surveys and documentation. The data analysis technique was carried out using descriptive statistical analysis using a percentage formula which was then translated into narrative form. This research concludes that students' attitudes towards earthquake and tsunami disaster mitigation are good with a percentage of 72.4%.